Comparison of 2.0 mg/kg/day and 0.5 mg/kg/day immunosuppressive dexamethasone protocols as initial treatment for dogs with MUO - Prikryl, Miroslav; Ferrini, Sara; Srenk, Petr (Frontiers in Veterinary Science, 2025)
IntroductionCanine meningoencephalitis of unknown origin (MUO) is a common immune-mediated neurological disorder primarily treated with corticosteroids. However, the optimal initial dosing regimen remains unclear.MethodThis prospective, randomized, parallel-group study evaluated the short-term clinical efficacy and gastrointestinal (GIT) safety of two intravenous dexamethasone dosing protocols (0.5 mg/kg/day vs. 2.0 mg/kg/day) in dogs diagnosed with MUO. Neurological and GI scoring systems were used to assess outcomes over a four-day hospitalization period.ResultsSixty dogs were enrolled and randomly assigned to either the 0.5 mg/kg/day (n = 30) or 2.0 mg/kg/day (n = 30) dexamethasone group. Neurological improvement was observed in 57 (95.0%) dogs, while 3 (5.0%) deteriorated, including 2 (3.3%) that died. No significant difference in neurological score changes was found between groups. Among the 58 survivors, 17 (28.3%) developed GIT signs, with 11 dogs in the 2.0 mg/kg/day group and 6 in the 0.5 mg/kg/day group. There was no significant difference in the incidence of GIT signs between groups, nor in the GIT score changes over time.DiscussionThis study has not identified a significant difference in short term outcome using different dosing protocols of dexamethasone in dogs diagnosed with MUO. Further studies with larger sample sizes and extended follow-up periods are warranted to investigate the potential dose-dependent effects of dexamethasone on both neurological and GIT outcomes.